Divergence of host range and biological properties between natural isolate and full‐length infectious cDNA clone of the Beet mild yellowing virus 2ITB. (16th July 2013) - Klein, Elodie; Brault, Véronique; Klein, Delphine; Weyens, Guy; Lefèbvre, Marc; Ziegler‐Graff, Véronique; Gilmer, David
Summary: Plant infection by poleroviruses is restricted to phloem tissues, preventing any classical leaf rub inoculation with viral RNA or virions. Efficient virus inoculation to plants is achieved by viruliferous aphids that acquire the virus by feeding on infected plants. The use of promoter‐driven infectious cDNA is an alternative means to infect plants and allows reverse genetic studies to be performed. Using Beet mild yellowing virus isolate 2ITB (BMYV‐2ITB), we produced a full‐length infectious cDNA clone of the virus (named BMYV‐EK) placed under the control of the T7 RNA polymerase and the Cauliflower mosaic virus 35S promoters. Infectivity of the engineered BMYV‐EK virus was assayed in different plant species and compared with that of the original virus. We showed that in vitro ‐ or in planta ‐derived transcripts were infectious in protoplasts and in whole plants. Importantly, the natural aphid vector Myzus persicae efficiently transmitted the viral progeny produced in infected plants. By comparing agroinoculation and aphid infection in a host range assay, we showed that the engineered BMYV‐EK virus displayed a similar host range to BMYV‐2ITB, except for Nicotiana benthamiana, which proved to be resistant to systemic infection with BMYV‐EK. Finally, both the BMYV‐EK P0 and the full‐length clone were able to strongly interfere with post‐transcriptional gene silencing.